2014
DOI: 10.1155/2014/429836
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Pricing and Ordering Policy for Two Echelon Varying Production Inventory System

Abstract: The paper proposes a two-stage supply chain model for price sensitive demand in imperfect production system while manufacturer and supplier are the members of the chain. The supplier screens the raw materials first and supplies good materials to the manufacturer at a constant rate. The production rate varies randomly within a finite interval. The inventory cycle of the manufacturer starts with shortages and production and it finishes with shortages again, in which shortages are partially backlogged. We conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…It is worth to mention, that there is a sufficient amount of research papers devoted to peculiarities of inventory management in multi-level systems (Guo and Li, 2014;Lai et al, 2014;Pal et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It is worth to mention, that there is a sufficient amount of research papers devoted to peculiarities of inventory management in multi-level systems (Guo and Li, 2014;Lai et al, 2014;Pal et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“… the research of environment factors, specifically, the demand characteristics and inflationary process impact on parameters of two-level inventory disposition system (for instance, research of Smith and Dekker (1997), Gumus and Guneri (2009), Guo and Li (2014);  the algorithmization of multilevel systems management methods, including the use of wellknown logistic technologies (within a framework of DPR systems, the researches on supply schedule algorithm were made by Yoo et al (1997), the supply parameter calculation according to the JIT technology is presented in work of Yang and Lin (2010), the issues of the algorithmic platform forming of the examined systems management are studied in the works of Caggiano et al (2009);  the development of methodology for the multilevel systems management based on the optimization models (Fahimnia et al, 2008;Pal et al, 2014;Lai et al, 2014). At the same time, within the view point of a search of the efficient methods for the increase of competitiveness and economical subjects activity effectiveness, the most productive direction is one that is based on the logistic integration conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Pal et al [21] investigated two echelon production inventory model where selling price and ordering size are decision variables. De et al [22] suggested an EOQ model for Phase Inventory system with induced demand and periodic cycle length. Sana [23] analyzed an EOQ model for uncertain demand for limited capacity of own warehouse, and the rented warehouse is considered, if needed.…”
Section: Introductionmentioning
confidence: 99%